THE CONSTITUTION OF THE RUSSIAN FEDERATION IN THE SYSTEM OF LEGAL REGULATION OF FAMILY RELATIONS - RABETS Anna Maksimovna (Правовое государство: теория и практика, 2023)
The article justifies the systemic role of the Constitution of the Russian Federation as a legal basis for regulating family relations and as a direct source of family law. The study is carried out with a view to determine the place of constitutional norms in the system of family law, their significance for the formation of goals, objectives and principles of legal regulation of family relations, for their direct regulation, as well as the place of the Constitution of the Russian Federation as a normative legal act in the system of family law. To achieve this goal, methods of historical, systemic and comparative legal analysis of legal norms contained in various branches of the legislation of the Russian Federation and in the family legislation of a number of foreign states are used. The study concludes that the Constitution of the Russian Federation plays a dominant role in legal regulation of family relations, presiding over the legal system of the Russian Federation as a whole and the system of family law as an independent branch of Russian law, as well as a two-tier system of family law, including the constitutions and charters of the constituent entities of the Russian Federation. It is also concluded that the Constitution of the Russian Federation as a source of family law contains rules governing family relations, reproduced in the Family Code of the Russian Federation as the principles of family law, plays the role of a direct normative legal act that regulates family relations and is applied in resolving specific family law disputes. At the constitutional level, the integration into the mechanism of legal regulation of family relations of other social regulators is ensured: traditional family values, national customs, traditions, etc., the inclusion of international treaties in the system of family law of the Russian Federation, their priority, direct action and interpretation by the Constitutional Court of the Russian Federation. It is proposed to enshrine at the constitutional level and in the family law of the Russian Federation the human right to marriage and family.